2019
DOI: 10.1111/jvim.15557
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous and subcutaneous metastasis of appendicular osteosarcoma in dogs: 20 cases

Abstract: Background Metastasis of appendicular osteosarcoma is most common to the lungs and is generally considered a terminal event in dogs. Behavior and prognosis associated with cutaneous or subcutaneous metastases (CSM) is poorly defined. Objective Describe the population and gather prognostic information regarding appendicular osteosarcoma with CSM in dogs. Animals Twenty dogs with appendicular osteosarcoma and CSM. Methods Retrospective case series. Medical records were searched to identify dogs diagnosed with ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…One further significant finding of the review was the evidence which shows lack of efficacy for toceranib in canine OSA. Four studies regarding the use of toceranib in dogs with metastatic OSA were identified and based on the results it was one of the most well described tumours 28,40–42 . While a study showed that toceranib can slightly inhibit cell growth in vitro, 87 the results of three of the clinical studies did not show promising results 40–42 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One further significant finding of the review was the evidence which shows lack of efficacy for toceranib in canine OSA. Four studies regarding the use of toceranib in dogs with metastatic OSA were identified and based on the results it was one of the most well described tumours 28,40–42 . While a study showed that toceranib can slightly inhibit cell growth in vitro, 87 the results of three of the clinical studies did not show promising results 40–42 .…”
Section: Discussionmentioning
confidence: 99%
“…Four studies regarding the use of toceranib in dogs with metastatic OSA were identified and based on the results it was one of the most well described tumours. 28,[40][41][42] While a study showed that toceranib can slightly inhibit cell growth in vitro, 87 the results of three of the clinical studies did not show promising results. [40][41][42] Multiple tyrosine kinase inhibitors, including sorafenib, apatinib, pazopanib and regorafenib, have been used in people with OSA with some encouraging findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although few cases involving dogs, cats, and rabbits with extraskeletal OSA (primary or metastatic) have been reported, cutaneous and subcutaneous metastasis (CSM) of dogs with primary appendicular OSA is an uncommon finding. A retrospective study by Parachini‐Winter et al 2 concluded that CSM can be the first site of metastasis with a possible predilection for the trunk and ventrum, and suggested that subcutaneous tissues are more commonly affected than the dermis.…”
Section: Discussionmentioning
confidence: 99%
“…Most metastasize to the lung (50%-85%); other reported locations include distant bone, regional lymph nodes, liver, and skin (dermis/subcutis). 24,35,105,131 Many canine patients develop metastases to multiple tissue sites (Figs. [17][18][19].…”
Section: Comparative Canine Os Researchmentioning
confidence: 99%